Defense mechanisms of persons with locomotor disabilities - Eranimos, Boban; Thankappan, Surya (Journal of Biomedical Sciences, 2019)
Background: According to World Health Organization 1, billion people -15% of the World population lives with various disabilities. Disabilities restricts individual’s participation of social life and this create limiting the maximum utilization of resources and hence the person crippled with psychological issues. Persons with disabilities were used various defense mechanisms as coping strategies to survive and compensate with their disabilities. The present study investigates the types of defense mechanisms used by persons with locomotor disabilities. Materials and methods: The total sample consists of 100 participants which include 50 males and 50 females. Among them 46 participants were congenitally disabled and 54 were acquired disabled. The participant’s age ranges between 18-60 years. The descriptive survey method was used for the present study and purposive sampling method adopted for sample selection. Defensive Behaviour Rating Scale (Sathya Giri Rajan, 1991) was used for data collection. The data was analysed by using Statistical Package for Social Sciences (SPSS) Version 16 for windows. Results: Female participants with locomotor disability have reported more reaction formation than male participants with locomotor disability. In the comparison of defense mechanisms of participants with locomotor disability with respect to their gender, male participants have reported more compensation, projection, identification, belittling and reaction formation and significantly lower repression than females. Females have reported significantly more daydreaming than males. Persons with congenital disability have higher sublimation than persons with an acquired disability. Conclusion: Researchers have long been fascinated by man’s defense mechanisms. Defense mechanisms are commonly used to protect the sense of self and help to defend people from painful emotions. In the present study, the investigator attempts to find out defense mechanisms of persons with locomotor disability and evaluation were made how they cope with the situation in relation to their nature of disability. The present study found that people with locomotor disability use both adaptive and maladaptive defense mechanisms, predominantly maladaptive defenses.